SHOPPER TYPOLOGY ON THE RELATIONSHIP BETWEEN SHOPPING MALL ATTRACTIVENESS AND SHOPPER PATRONAGE - Ng, KEITH Y.N. (Centre For Tourism Planning and Development, 2013)
The rapid growth of China's economy has fuelled the growth of the residential property market in China. Together with the growth of residential properties, developers are also investing in Shopping Malls to cater to residential needs. However, the lack of understanding shoppers has seen homogenous types of shopping malls built. This not only meant an increase in competition but also replicating resources; both of which meant not meeting the financial objectives intended. The purpose of this study is to examine the impact of shopper typology on the relationship between shopping mall attractiveness and shopper patronage. The results will help developers of shopping malls must pay close attention to the types of shopper that they intend to serve and ensure long term success of developing shopping malls.